Human T-cell lymphotropic virus type I (HTLV-I) proviral DNA viral load among asymptomatic patients and patients with HTLV-I-associated myelopathy/tropical spastic paraparesis - Montanheiro, P.A.; Penalva de Oliveira, A.C.; Posada-Vergara, M.P.; Milagres, A.C.; Tauil, C.; Marchiori, P.E.; Duarte, A.J.S.; Casseb, J. (Brazilian journal of medical and biological research, 2005)
To evaluate the human T-cell lymphotropic virus type I (HTLV-I) proviral DNA load among asymptomatic HTLV-I-infected carriers and patients with HTLV-I-associated myelopathy/tropical spastic paraparesis (HAM/TSP), real time PCR using TaqMan probes for the pol gene was performed in two million peripheral blood mononuclear cells (PBMC). The albumin gene was the internal genomic control and MT2 cells were used as positive control. The results are reported as copies/10,000 PBMC, and the detection limit was 10 copies. A total of 89 subjects (44 HAM/TSP and 45 healthy HTLV-I-infected carriers) followed up at the Institute of Infectious Diseases "Emilio Ribas" and in the Neurology Division of Hospital of Clínicas were studied. The asymptomatic HTLV-I-infected carriers had a median number of 271 copies (ranging from 5 to 4756 copies), whereas the HAM/TSP cases presented a median of 679 copies (5-5360 copies) in 10,000 PBMC. Thus, HAM/TSP patients presented a significantly higher HTLV-I proviral DNA load than healthy HTLV-I carriers (P = 0.005, one-way Mann-Whitney test). As observed in other persistent infections, proviral DNA load quantification may be an important tool for monotoring HTLV-I-infected subjects. However, long-term follow-up is necessary to validate this assay in the clinical setting.